A pneumatic-muscle-actuator-driven knee rehabilitation device for CAM therapy - Martens, Mirco; Zawatzki, Johannes; Seel, Thomas; Boblan, Ivo (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2019)
In this paper a novel knee joint rehabilitation device made for controlled active motion (CAM) therapy is presented and tested. More precisely, the system is a redesign of an originally passive CAM device, called CAMOped. Instead of a break, the adjustable resistance, which is needed for CAM therapy, is now provided via a torque-controlled pneumatic-muscle-actuator-driven joint. These actuators are inherently compliant and can produce both a variable restistance and, by co-contraction, a variable stiffness. It will be shown that, by measuring the foot contact forces and using them as feedback information, the foot load can be adjusted very precisely up to 100 N. Furthermore, it will be demonstrated that, in contrast to passive systems, the presented active systems is capable of varying the resistance while the device is in use. This facilitates adapting the resistance to the patient's needs in real time and to use joint-angle-or foot-position-dependent resistance curves.
CRIS-Team Scopus Importer:2021-03-31